Applications of transcriptomics and proteomics in understanding fish immunity. Issue 77 (June 2018) - Ye, Hua; Lin, Qingsong; Luo, Hui
Abstract: With the development of intensive aquaculture, economic losses increasingly result from fish mortality due to pathogen infection. In recent years, a growing number of researchers have used transcriptomic and proteomic analyses to study fish immune responses to exogenous pathogen infection. Integrating transcriptomic and proteomic analyses provides a better understanding of the fish immune system including gene expression, regulation, and the intricate biological processes underlying immune responses against infection. This review focuses on the recent advances in the fields of transcriptomics and proteomics, which have contributed to our understanding of fish immunity to exogenous pathogens. Graphical abstract: Image 1